2021
DOI: 10.1007/s10444-021-09905-3
|View full text |Cite
|
Sign up to set email alerts
|

Optimal error estimates for Legendre expansions of singular functions with fractional derivatives of bounded variation

Abstract: This paper concerns optimal error estimates for Legendre polynomial expansions of singular functions whose regularities are naturally characterised by a certain fractional Sobolev-type space introduced in [34, Math. Comput., 2019]. The regularity is quantified as the Riemann-Liouville (RL) fractional integration (of order 1 − s ∈ (0, 1)) of the highest possible integer-order derivative (of order m) of the underlying singular function that is of bounded variation. Different from Chebyshev approximation, the usu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 45 publications
(83 reference statements)
1
4
0
Order By: Relevance
“…To test the convergence rate on direction of 𝑣, we take 𝜖 = 𝜔 = 1, 𝜏 = 0.005, Ω 𝑥 = (0, 2𝜋), Ω 𝑣 = (−8, 8) and fix 2𝑀 + 1 = 13 Fourier modes, but run up 𝑇 = 0.1. In Figure 2, it shows that the convergence orders in 𝐿 2 norm, 𝐿 ∞ norm are 𝑠 + 1 2 and 𝑠, respectively, and the convergence behaviours are consistent with the Legendre approximation results for such functions with limited regularity (see e.g., [20]).…”
Section: Numerical Results For the Cnfl Schemesupporting
confidence: 77%
“…To test the convergence rate on direction of 𝑣, we take 𝜖 = 𝜔 = 1, 𝜏 = 0.005, Ω 𝑥 = (0, 2𝜋), Ω 𝑣 = (−8, 8) and fix 2𝑀 + 1 = 13 Fourier modes, but run up 𝑇 = 0.1. In Figure 2, it shows that the convergence orders in 𝐿 2 norm, 𝐿 ∞ norm are 𝑠 + 1 2 and 𝑠, respectively, and the convergence behaviours are consistent with the Legendre approximation results for such functions with limited regularity (see e.g., [20]).…”
Section: Numerical Results For the Cnfl Schemesupporting
confidence: 77%
“…The error estimate of other orthogonal projections such as Legendre, Gegenbauer and Jacobi projections has attracted attention in recent years (see, e.g., [1,16,29,30,32,33]). In [29, Figure 3] it has been observed that the error curves of Legendre projections illustrate similar character as that of Chebyshev projections.…”
Section: Other Orthogonal Projectionsmentioning
confidence: 99%
“…It is clear that the test functions in (3.4) also belong to this space and f 4 ∈ H 4 , f 5 ∈ H 5 and f 6 ∈ H 3 . This space is preferable when developing error estimates for various orthogonal polynomial approximations to differentiable function (see, e.g., [16,17,27,30,33]). Comparing the space H m and the assumption of piecewise analytic functions, which one is better in the sense that optimal rate of convergence of S λ n (f ) can be predicted?…”
Section: Optimal Rate Of Convergence Of Gegenbauer Projections For Pi...mentioning
confidence: 99%
“…Moreover, to the best of the author's knowledge, the sharpness of the derived error estimates has not been addressed. For the latter approach, a remarkable advantage is that some computable error bounds of S n (f ) can be established (see, e.g., [1,16,17,27,28,30,31,32,33,35]). However, as shown in [30,31], the convergence rate predicted by this approach may be overestimated for differentiable functions.…”
Section: Introductionmentioning
confidence: 99%